Designing in students’ training in the field of law - S. E. Titor (Вестник университета)
According to the Ministry of Labor and Social Protection of the Russian Federation, there is an opinion among leading employers that only 8 % of professional educational organizations graduates are fully prepared to perform their job duties. Modern economy, especially in the stage of import substitution and sanctions, requires a strong and highly qualified competitive employee. Modern vocational education has special requirements, it needs transformation. Professional competencies of modern graduates continue to be the center of attention. Continuous development of techniques and technologies requires mobility, flexibility, and timely actualization from professional education. The study analyzes experience of Law project training of students as a way to increase the demand for law graduates in labor market. The analysis has been conducted on legal specialists training.